BIFIDOBACTERIA AND THEIR BIOLOGICAL PROPERTIES - О. А. Полтавська; Н. К. Коваленко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2008)
Literature data, concerning the study of bifidobacterial biology are represented in the review. The information about development and modern condition of bifidobacterial taxonomy and about phenotypic characters of this group of microorganisms is expounded. The analysis of the studies described the investigation of antagonistic, adhesive properties of bifidobacteria is conducted. The question of the use of bifidobacteria in composition of probiotic preparations is taken up.